Basics of using natural basalt ore in the territory of Uzbekistan as a filler for sewage pipes - Tavashov Shaxzod Xojaxmatovich; Jumaeva Anora Adham kizi (Zien Journals, 2023)
As the development of today's industrial development in the world increases, so does the demand for opening opportunities, and the most important demand is increasing. As the natural resources are decreasing year by year, it is an important task to find large-scale products that can replace them. The volume of production of polymer composite materials, which make up many industrial enterprises and are part of their production products, is increasing day by day. Therefore, the localization of the most basic components in the production of polymer products, i.e. fillers, thermostabilizers and plasticizers, is of great importance. Substitution of raw materials with lower prices leads to economic gains as well as significant changes in terms of quality
Keywords: basalt; filler; polyvinyl chloride; modification